Răspuns :
[tex]a - primul \: copil[/tex]
[tex]b - al \: doilea \: copil[/tex]
[tex]c - al \: treilea \: copil[/tex]
[tex]a + b + c = 98[/tex]
[tex]a + b = 76[/tex]
[tex]a = 76 - b[/tex]
[tex]b + c = 65[/tex]
[tex]c = 65 - b[/tex]
[tex]76 - b + b + 65 - b = 98[/tex]
[tex] - b + b - b = 98 - 76 - 65[/tex]
[tex] - b = - 43 \: | \times ( - 1)[/tex]
[tex]b = 43[/tex]
[tex]a = 76 - b[/tex]
[tex]a = 76 - 43[/tex]
[tex]a = 33[/tex]
[tex]c = 65 - b[/tex]
[tex]c = 65 - 43[/tex]
[tex]c = 22[/tex]
[tex]b - al \: doilea \: copil[/tex]
[tex]c - al \: treilea \: copil[/tex]
[tex]a + b + c = 98[/tex]
[tex]a + b = 76[/tex]
[tex]a = 76 - b[/tex]
[tex]b + c = 65[/tex]
[tex]c = 65 - b[/tex]
[tex]76 - b + b + 65 - b = 98[/tex]
[tex] - b + b - b = 98 - 76 - 65[/tex]
[tex] - b = - 43 \: | \times ( - 1)[/tex]
[tex]b = 43[/tex]
[tex]a = 76 - b[/tex]
[tex]a = 76 - 43[/tex]
[tex]a = 33[/tex]
[tex]c = 65 - b[/tex]
[tex]c = 65 - 43[/tex]
[tex]c = 22[/tex]
A+B+C=98 /
A+B=76 /=>
B+C=65 /
=>76+C=98
C=98-76
C=22=>B+C=65
B+22=65
B=65-22
B=43=>A+B=76
A+43=76
A=76-43
A=33
A+B=76 /=>
B+C=65 /
=>76+C=98
C=98-76
C=22=>B+C=65
B+22=65
B=65-22
B=43=>A+B=76
A+43=76
A=76-43
A=33